The Free Particle Solution for NonLinear Master Schrödinger - Prayitno, T. B. (Jurnal Spektra, 2010)
The solution of free particle has been studied by solving nonlinear master Schrödinger equation. This equation actually consists of two properties, Hamilton-Jacobi equation and continuity equation which describe two classical balance equations. In other words, those two equations were assumed to be hold in quantum level. Unfortunately, there are several properties in ordinary quantum mechanics must be ignored, such as first principle quantization and superposition principle. In this paper we briefly review some important study of the characteristics of nonlinear master Schrödinger equation. In addition, we also have proposed two kinds of free particle solution for the nonlinear master Schrödinger and founded that the solution poses a plane wave solution. Keywords: nonlinear master Schrödinger, free particle, Hamilton-Jacobi.